Enhancing Brioche Bread with Emulsified Seed and Nut Oils: Nutritional and Sustainable Benefits - Elena Martínez; María Esther Martínez-Navarro; José E. Pardo; Adrian Rabadan; Manuel Álvarez-Ortí (Applied Sciences)
This study evaluates the effectiveness of an oil-in-water emulsion formulated from water and seed and nut oils as a substitute for butter in the formulation of brioche bread. First, the selected oils were physicochemically characterized. In the brioche, animal fat was fully and partially replaced, and the effects were analyzed at the physical, chemical, and sensory levels. The new formulations exhibited increased lightness, a softer crumb, improved cohesiveness, and greater expansion compared to the control, resulting in fluffier and lighter brioches. Nutritionally, the seed and nut oil brioches showed a lower fat content and lower energy value, but higher protein and carbohydrate levels. The lipid profile was enhanced, with a higher proportion of unsaturated fatty acids, which positively impacted two heart-friendly indices and increased the vitamin E content. This improvement potentially allows the food industry to apply health claims to product labeling. Regarding sensory analysis, in all cases, the reformulated brioches scored higher than the control sample in terms of external appearance, although there remained a preference for the flavor and aroma of the traditional version, which could be mitigated by adding flavor compounds such as diacetyl. This study differs from previous research by using a seed and nut oil emulsion instead of non-emulsified oils, improving the texture and stability of brioche bread, an achievement not consistently reported in prior studies. Additionally, it emphasizes sustainability by offering a plant-based alternative that addresses the growing consumer demand for vegan and eco-friendly products while providing enhanced nutritional benefits that support potential health claims.